Bestseller e non solo: Le funzioni sociali dei romanzi di Guido Da Verona - Kriston, Dorottya Anna (Verbum – Analecta Neolatina, 2022)
Guido Da Verona (1881–1939), “the handmaids’ D’Annunzio” was one of the most important best-selling authors in Italy in the 1920s. A bestseller is a book that satisfies the demands of the masses of readers as it operates as a mirror of society, and it may take on some new functions. This paper intends to demonstrate the social roles of Da Verona’s œuvre. He was a spokesman of the middle-class, and expressed the tensions between intellectuals and philistines. His novels could also have practical uses: they could help the readers’ mourning process by representing luxury, peace and inevitable tragical events at the same time. The paper shows that the approach of the sociology of literature (based on the theories of Robert Escarpit) is necessary in the research on mass literature.